PENCARIAN PRODUK E-COMMERCE BERDASARKAN JUDUL DAN DESKRIPSI MENGGUNAKAN VECTOR SPACE MODEL - Ayuni Asistyasari (Jupiter: Journal of Computer & Information Technology, 2020)
E-Commerce in Indonesia has increased every year, especially B2C sales and this is directly proportional to the increasing number of e-commerce sites in Indonesia. One of the things that this site offers is the ease of finding the product you want to find. However, in several tests conducted, it turns out that some Indonesian e commerce sites are unable to search for products based on the description keyword. Therefore, the writer tries to do this research using the VSM algorithm and produces an accuracy of 60%, a precision of 72.73%, and a recall of 80%.